DAMPAK LINGKUNGAN PEMBANGUNAN PABRIK FARMASI XYZ DI JAWA TENGAH - Muhamad Yusuf (EnviroScienteae, 2022)
The construction of a pharmaceutical factory has an impact in the form of a decline in the surrounding environment. This study aims to determine the environmental impact arising from construction a pharmaceutical factory. A descriptive qualitative approach was used. Analyses show that the development meets the environmental baseline in terms of the geo-physical aspect, but for the water around the location for several parameters it is above the quality standard, in terms of the biological environmental baseline it meets as a project development area, and In terms of the socio-economic and cultural components of the community. Some of the components that influence and cause a decline in development include: Physical and Chemical Environment, community social environment, environmental health. To overcome the problems that arise, recommendations are given for the water that will be used for factory operations by making a storage pond to accommodate rainwater and treated water from the WWTP so that it can be processed into clean water in the RWTP unit and management is carried out on all components of activities that have an impact. As a result, the pharmaceutical factory can be constructed according to plan.